Expanding oil palm cultivation in Indonesia: changing local water cycles raises risks of droughts and floods - Jennifer Merten; Alexander Röll; Surya Tarigan; Dirk Hölscher; Jonas Hein (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
During El Ni\~no in 2015, devastating forest fires in Indonesia directed international attention towards land use changes and deforestation on the archipelago. At least partially a result of clearing land for plantation estates, those fires spurred debate about the sustainability of palm oil, which is the most traded vegetable oil. Recently, seven European governments signed the Amsterdam Declaration. Its signatories, including Germany, committed themselves to helping the private sector to achieve a fully sustainable palm oil supply chain by 2020. Despite progress made in talks on sustainability, little is visible on the ground. To the contrary, as the Indonesian case shows, that palm oil expansions can cause soil and water resources to degrade. Especially weak law enforcement poses a major challenge to a sustainable production of oil palm. At the same time, the oil palm business has been expanding rapidly in Latin America and West Africa. For smallholders oil palm cultivation is an attractive land use option that requires little labour input and allows them to engage in off-farm income activities. Current discussions about the ecological impacts of expanding palm oil production focus on how it destroys primary forest and peatlands, increases greenhouse gas (GHG) emissions and reduces biodiversity. Little attention has been paid to concerns that oil palm plantations severely impact local water resources and increase flood risks. This briefing paper makes use of a recent interdisciplinary publication (Merten et al., 2016) and extensive fieldwork to analyse the way expanding palm oil production impacts the hydrological cycle. It also discusses water management criteria in certification schemes and national regulations. Measurements of eco-hydrological processes and observations of Indonesian farmers indicate that large-scale oil palm monoculture has long-term negative consequences for smallholder farming systems and the water supplies of rural communities. Our interdisciplinary study has revealed that: local populations report water shortages in dry seasons in the wake of new oil palm plantations; expanding oil palm plantations leads to more frequent floods; intensive monoculture plantation systems severely degrade the soil, impeding the recharge of groundwater reservoirs and increasing surface runoff; and oil palm cultivation impacts the local hydrological cycle more severely than other crops. Based on these findings we recommend that: The European Union (EU) should set mandatory sustainability standards for all palm oil products. Water and soil management should have prominent roles in environmental impact assessments and sustainability standards. Sustainability standards for agrofuels should be better monitored. If compliance cannot be guaranteed, the EU should consider a temporary ban on using palm oil for agrofuel production.
Keywords: 330; Wasser; Landwirtschaft und ländliche Entwicklung